(untitled) (Analysis in Theory and Applications, 2017)
In this paper, firstly, a notion of a class of generalized weighted pseudo almost periodic function is introduced, then we investigate some basic and essential properties of the space that consists of these functions. Finally, we study the existence of weighted pseudo almost periodic solutions to hematopoiesis model with time-varying delay.